Isolated pituitary neurosarcoidosis: A case report and review of the literature [İzole pituiter nörosarkoidoz: Olgu sunumu ve literatürün gözden geçirilmesi] - (:unkn) unknown (My University, 2011)
Sarcoidosis is a multisystem granulomatous disorder, commonly affecting young adults and usually presenting with bilateral hilar lymphadenopathy and pulmonary infiltration. Central nervous system (CNS) involvement is extremely rare. The cause of sarcoidosis is unknown. The diagnosis of sarcoidosis is firmly established when histopathological evidence of non-caseating granulomas in affected organs supports compatible clinicoradiographic findings. Here, we present a case of a 30-year-old woman referred to our clinic with amenorrhea and polyuria. The radiological appearance of a lesion involving the pituitary stalk was an image of inflammatory infiltration, which is pathognomic for sarcoidosis, syphilis, tuberculosis and foreign body granulomatosis. Laboratory tests were done to rule out syphilis and tuberculosis. A possible diagnosis was sarcoidosis. When we searched other systems for the involvement of sarcoidosis, lungs, lymph nodes, skin and eyes were not involved by the disease. Histopathological examination of a transcranial incisional biopsy revealed a non-caseating granuloma, consisting of macrophages, epithelioid cells, and multinucleated giant cells that secrete cytokines. Around this central core, CD4 and CD8 lymphocytes, B lymphocytes, plasma cells, and fibroblasts were detected. The diagnosis was neurosarcoidosis. We present this case to draw attention to the possibility of isolated neurosarcoidosis as the differential diagnosis of pituitary lesions and review recent advances in the investigation, diagnosis and treatment of this condition. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Neurosarcoidosis; Non-caseating granulomas; Pituitary lesions; Sarcoidosis